Safety and efficacy of aneurysm treatment with WEB in the cumulative population of three prospective, multicenter series - Pierot, Laurent; Moret, Jacques; Barreau, Xavier; Szikora, Istvan; Herbreteau, Denis; Turjman, Francis; Holtmannspötter, Markus; Januel, Anne-Christine; Costalat, Vincent; Fiehler, Jens; Klisch, Joachim; Gauvrit, Jean-Yves; et al. (Journal of neurointerventional surgery, 2018)
BackgroundFlow disruption with the WEB is an innovative endovascular approach for treatment of wide-neck bifurcation aneurysms. Initial studies have shown a low complication rate with good efficacy.PurposeTo report clinical and anatomical results of the WEB treatment in the cumulative population of three Good Clinical Practice (GCP) studies: WEBCAST (WEB Clinical Assessment of Intrasaccular Aneurysm), French Observatory, and WEBCAST-2.MethodsWEBCAST, French Observatory, and WEBCAST-2 are single-arm, prospective, multicenter, GCP studies dedicated to the evaluation of WEB treatment. Clinical data were independently evaluated. Postoperative and 1-year aneurysm occlusion was independently evaluated using the 3-grade scale: complete occlusion, neck remnant, and aneurysm remnant.ResultsThe cumulative population comprised 168 patients with 169 aneurysms, including 112 female subjects (66.7%). The patients' ages ranged between 27 and 77 years (mean 55.5±10.2 years). Aneurysm locations were middle cerebral artery in 86/169 aneurysms (50.9%), anterior communicating artery in 36/169 (21.3%), basilar artery in 30/169 (17.8%), and internal carotid artery terminus in 17/169 (10.1%). The aneurysm was ruptured in 14/169 (8.3%). There was no mortality at 1 month and procedure/device-related morbidity was 1.2% (2/168). At 1 year, complete aneurysm occlusion was observed in 81/153 aneurysms (52.9%), neck remnant in 40/153 aneurysms (26.1%), and aneurysm remnant in 32/153 aneurysms (20.9%). Re-treatment was carried out in 6.9%.ConclusionsThis series is at the moment the largest prospective, multicenter, GCP series of patients with aneurysms treated with WEB. It shows the high safety and good mid-term efficacy of this treatment.Clinical trial registrationFrench Observatory: Unique identifier (NCT18069); WEBCAST and WEBCAST-2: Unique identifier (NCT01778322).